Plasmodium falciparum VAR2CSA-Specific IgG Subclass Responses Reflect Protection Against Low Birth Weight and Pregnancy-Associated Malaria - Tornyigah, Bernard; d’Almeida, Tania; Escriou, Guillaume; Viwami, Firmine; Fievet, Nadine; Luty, Adrian J. F.; Massougbodji, Achille; Nielsen, Morten A.; Deloron, Philippe; Tuikue Ndam, Nicaise (Frontiers in Immunology, 2021)
Sequestration of Plasmodium falciparum-infected erythrocytes expressing the VAR2CSA antigen in the placenta results in poor pregnancy outcomes, including low birth weight and maternal anemia. Antigen-specific antibody-mediated immunity is acquired during successive pregnancies. Thus, evaluating VAR2CSA-specific IgG profiles among pregnant women will increase knowledge on the immunological mechanisms associated with protection, and help in the development of VAR2CSA-based placental malaria vaccines. Using the PAMVAC candidate vaccine antigen, we assessed anti-VAR2CSA IgG subclass responses of a cohort of pregnant Beninese, and analyzed their relationships with pregnancy outcomes. Cytophilic IgG1 and IgG3 responses were the most frequent, with prevalence ranging from 28% (IgG3) up to 50% (IgG1). Elevated levels of VAR2CSA-specific total IgG and cytophilic IgG3 during pregnancy were consistently associated with higher birth weights, whilst high levels of IgG4 were associated with a reduced risk of placental infections. This suggests that protective anti-VAR2CSA IgG responses are coordinated between both cytophilic and non-cytophilic antibodies.